2017
DOI: 10.1073/pnas.1619667114
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37 suppresses the osteogenic responses of human aortic valve interstitial cells in vitro and alleviates valve lesions in mice

Abstract: Calcific aortic valve disease is a chronic inflammatory process, and aortic valve interstitial cells (AVICs) from diseased aortic valves express greater levels of osteogenic factors in response to proinflammatory stimulation. Here, we report that lower cellular levels of IL-37 in AVICs of diseased human aortic valves likely account for augmented expression of bone morphogenetic protein-2 (BMP-2) and alkaline phosphatase (ALP) following stimulation of Toll-like receptor (TLR) 2 or 4. Treatment of diseased AVICs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 43 publications
4
80
0
Order By: Relevance
“…In a recent study, we observed that recombinant IL-37 inhibits the production of pro-osteogenic mediators (bone morphogenic protein 2 and alkaline phosphatase) in human AVICs exposed to TLR2 and TLR4 agonists, and that the antiosteogenic effect of IL-37 is due to inhibition of ERK1/2 and NF-κB (23). The antiinflammatory effect of IL-37 observed in the present study is correlated with its inhibitory effect on NF-κB activation.…”
Section: Disclosuresupporting
confidence: 78%
See 2 more Smart Citations
“…In a recent study, we observed that recombinant IL-37 inhibits the production of pro-osteogenic mediators (bone morphogenic protein 2 and alkaline phosphatase) in human AVICs exposed to TLR2 and TLR4 agonists, and that the antiosteogenic effect of IL-37 is due to inhibition of ERK1/2 and NF-κB (23). The antiinflammatory effect of IL-37 observed in the present study is correlated with its inhibitory effect on NF-κB activation.…”
Section: Disclosuresupporting
confidence: 78%
“…IL-37 mRNA and protein are present in tissues of patients with inflammatory and autoimmune diseases, such as rheumatoid arthritis, atherosclerosis, Crohn's disease and lupus (21). In cells that overexpress IL-37, the inflammatory responses to a variety of proinflammatory stimuli are markedly attenuated (21,23). More important, mice carrying the human IL-37 gene (IL-37 transgenic mice) are protected against aortic valve lesions induced by proinflammatory stimuli (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IL-1b induces BMP2 and BMP4 that have been shown to reduce beta-cell function. By reducing levels of IL-1b and therefore BMP2, IL-37 may therefore improve betacell function (48). Together, this suggests that administration of IL-37 can reverse HFD-induced metabolic stress upon the islets, probably via a reduction of infiltrating macrophages and thereby production of beta-cell cytotoxic IL-1 and induction of BMP2 resulting in improved insulin homeostasis.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies show that inhibition of NF-κB reduces the release of inflammatory cytokines and inducible nitric oxide synthase (iNOS), and protects mice against lethal endotoxemia [12]. Our recent study demonstrates that IL-37 inhibits NF-κB activation induced by oxidized low-density lipoprotein in human aortic valve cells [40]. The in vitro data in the present study indicate that IL-37 represses the NF-κB response to TLR4 stimulation to modulate MCP-1 production in cardiac microvascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%